Tocilizumab for Severe Worsening COVID-19 Pneumonia: a Propensity Score Analysis - Roumier, Mathilde; Paule, Romain; Vallée, Alexandre; Rohmer, Julien; Ballester, Marie; Brun, Anne-Laure; Cerf, Charles; Chabi, Marie-Laure; Chinet, Thierry; Colombier, Marie-Alice; Farfour, Eric; Fourn, Erwan; et al. (Journal of clinical immunology, 2021)
Background High levels of serum interleukin-6 (IL-6) correlate with disease severity in COVID-19. We hypothesized that tocilizumab (a recombinant humanized anti-IL-6 receptor) could improve outcomes in selected patients with severe worsening COVID-19 pneumonia and high inflammatory parameters. Methods The TOCICOVID study included a prospective cohort of patients aged 16–80 years with severe (requiring > 6 L/min of oxygen therapy to obtain Sp02 > 94%) rapidly deteriorating (increase by ≥ 3 L/min of oxygen flow within the previous 12 h) COVID-19 pneumonia with ≥ 5 days of symptoms and C-reactive protein levels > 40 mg/L. They entered a compassionate use program of treatment with intravenous tocilizumab (8 mg/kg with a maximum of 800 mg per infusion; and if needed a second infusion 24 to 72 h later). A control group was retrospectively selected with the same inclusion criteria. Outcomes were assessed at D28 using inverse probability of treatment weighted (IPTW) methodology. Results Among the 96 patients included (81% male, mean (SD) age: 60 (12.5) years), underlying conditions, baseline disease severity, and concomitant medications were broadly similar between the tocilizumab ( n = 49) and the control ( n = 47) groups. In the IPTW analysis, treatment with tocilizumab was associated with a reduced need for overall ventilatory support (49 vs. 89%, wHR: 0.39 [0.25–0.56]; p < 0.001). Albeit lacking statistical significance, there was a substantial trend towards a reduction of mechanical ventilation (31% vs. 45%; wHR: 0.58 [0.36–0.94]; p = 0.026). However, tocilizumab did not improve overall survival (wHR = 0.68 [0.31–1.748], p = 0.338). Among the 85 (89%) patients still alive at D28, patients treated with tocilizumab had a higher rate of oxygen withdrawal (82% vs. 73.5%, wHR = 1.66 [1.17–2.37], p = 0.005), with a shorter delay before being weaned of oxygen therapy (mean 11 vs. 16 days; p < 0.001). At D28, the rate of patients discharged from hospital was higher in the tocilizumab group (70% vs. 40%, wHR = 1.82 [1.22–2.75]; p = 0.003). The levels of CRP and fibrinogen post therapy ( p < 0.001 for both variables) were significantly lower in the tocilizumab group (interaction test, mixed model). Rates of neutropenia (35% vs. 0%; p < 0.001) were higher in the tocilizumab group, yet rates of infections (22% vs. 38%, p = 0.089) including ventilator-acquired pneumonia (8% vs. 26%, p = 0.022) were higher in the control group. Conclusion These data could be helpful for the design of future trials aiming to counter COVID-19-induced inflammation, especially before patients require admission to the intensive care unit.